Emotional and Behavioral Outcomes in Childhood for Survivors of Invasive Group B Streptococcus Disease in Infancy: Findings From 5 Low- and Middle-Income Countries. (2nd November 2021) - Chandna, Jaya; Liu, Wan-Hsin; Dangor, Ziyaad; Leahy, Shannon; Sridhar, Santhanam; John, Hima B; Mucasse, Humberto; Bassat, Quique; Bardaji, Azucena; Abubakar, Amina; Nasambu, Carophine; Newton, Charles R; et al.
Abstract: Background: Survivors of invasive group B Streptococcus (iGBS) disease, notably meningitis, are at increased risk of neurodevelopmental impairment. However, the limited studies to date have a median follow-up to 18 months and have mainly focused on moderate or severe neurodevelopmental impairment, with no previous studies on emotional-behavioral problems among iGBS survivors. Methods: In this multicountry, matched cohort study, we included children aged 18 months to 17 years with infant iGBS sepsis and meningitis from health demographic surveillance systems, or hospital records in Argentina, India, Kenya, Mozambique, and South Africa. Children without an iGBS history were matched to iGBS survivors for sex and age. Our primary outcomes were emotional-behavioral problems and psychopathological conditions as measured with the Child Behavior Checklist (CBCL). The CBCL was completed by the child's primary caregiver. Results: Between October 2019 and April 2021, 573 children (mean age, 7.18 years) were assessed, including 156 iGBS survivors and 417 non-iGBS comparison children. On average, we observed more total problems and more anxiety, attention, and conduct problems for school-aged iGBS survivors compared with the non-iGBS group. No differences were found in the proportion of clinically significant psychopathological conditions defined by the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition). Conclusions: Our findings suggested that school-aged iGBS survivors experienced increased mild emotional behavioral problems that may affect children and families. At-risk neonates including iGBS survivors need long-term follow-up with integrated emotional-behavioral assessments and appropriate care. Scale-up will require simplified assessments that are free and culturally adapted.